Delayed photosensitivity in a child with erythropoietic protoporphyria : a case report. (October 2018) - Kiberd, James; Finlayson, Laura
Erythropoietic protoporphyria (EPP) is a genetically inherited disease that causes protoporphyrin accumulation in erythrocytes, skin, liver, bile, and stool. Clinically this manifests as photosensitivity with painful, edematous cutaneous porphyria. We present the case of a four-year-old boy with a delayed photosensitivity reaction to sunlight. In the evening following sun exposure, he would develop swelling and a violaceous rash on the dorsal surface of his hands and occasionally the helix of his ears. His reactions were severe, requiring morphine on more than one occasion prior to diagnosis. He later developed waxy depressed scars on his nose and cheeks. On laboratory investigation, both total and free protoporphyrin were elevated. Photosensitivity in EPP usually occurs minutes after sun exposure, but our patient had significantly delayed reactions. Genetic testing revealed mutation in the FECH gene that confirmed the diagnosis of EPP. Although rare, presentations of photosensitivity in the pediatric population should be carefully evaluated.